2012
DOI: 10.1016/j.ejphar.2012.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate modulates the locus ceruleus neuronal activity in freely behaving rat

Abstract: The electrophysiological properties of the locus coeruleus (LC) neurons in response to acute and chronic administration of methylphenidate (MPD) were investigated. The extracellular LC neuronal activities were recorded from non-anesthetized, freely behaving rats previously implanted bilaterally with permanent semi microelectrodes. The main findings were: (1) On experimental day 1 (ED1), 87% (94/108) of LC units significantly changed their firing rate after initial (acute) MPD (2.5 mg/kg, i.p.) administration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 86 publications
3
10
0
Order By: Relevance
“…The main behavioral findings of this study were that the same chronic dose of 0.6, 2.5, and 10.0 mg/kg methylphenidate elicited in some animals behavioral sensitization, and in others behavioral tolerance. This is comparable to observations using similar protocols (Claussen & Dafny,; Frolov et al, ;Jones & Dafny, ; Tang & Dafny, ; Venkarataman, Claussen, Joseph, & Dafny, ). In general, the ventral tegmental area and nucleus accumbens units responded to MPD with dose‐response characteristics: with increased MPD dosage more units responded to the drug, from less than 50% of units responding following acute 0.6 mg/kg MPD exposure to more than 70% of units responding following acute 10.0 mg/kg MPD exposure.…”
Section: Discussionsupporting
confidence: 88%
“…The main behavioral findings of this study were that the same chronic dose of 0.6, 2.5, and 10.0 mg/kg methylphenidate elicited in some animals behavioral sensitization, and in others behavioral tolerance. This is comparable to observations using similar protocols (Claussen & Dafny,; Frolov et al, ;Jones & Dafny, ; Tang & Dafny, ; Venkarataman, Claussen, Joseph, & Dafny, ). In general, the ventral tegmental area and nucleus accumbens units responded to MPD with dose‐response characteristics: with increased MPD dosage more units responded to the drug, from less than 50% of units responding following acute 0.6 mg/kg MPD exposure to more than 70% of units responding following acute 10.0 mg/kg MPD exposure.…”
Section: Discussionsupporting
confidence: 88%
“…Previous experiments have shown that daily saline injections for three weeks do not alter behavioral locomotor activity, sensory evoked neuronal potentials, or electrophysiological neuronal firing rates (Yang et al, 2006a;b;c;d). Therefore, the activity after saline injection was used as control for the drug effect (Claussen and Dafny 2012; Frolov et al, 2015; Jones and Dafny, 2013; Salek et al, 2012; Tang and Dafny 2012; 2013; Yang et al, 2006b, 2007). To determine if MPD induced a significant change/response, multiple methods were employed as follow: the mean activity after treatment needs to be at least two standard errors (S.E.)…”
Section: Methodsmentioning
confidence: 99%
“…difference from the control firing rate. Because the firing rates did not hold up to normality assumptions used to determine parametric or non-parametric, significance was based also on the critical ratio test ( C.R.=1E-CE+C=±1.96=p<0.05) (C = control, E = drug activity) (Chong et al, 2012; Claussen and Dafny 2012; Dafny, 1975; 1982; Frolov et al, 2015; Jones and Dafny, 2013; Salek et al, 2012; Tang and Dafny 2012; 2013; Yang et al, 2006a;b;c). The following comparisons were made, from the three (0.6, 2.5, 10.0 mg/kg MPD) groups 1) neuronal activity recorded from all animals 2) neuronal activity recorded from animals expressing behavioral sensitization, and 3) neuronal activity recorded from animals expressing behavioral tolerance, to chronic MPD exposure.…”
Section: Methodsmentioning
confidence: 99%
“…During the placement of electrodes, the LC unit activity was monitored using a grass P511 amplifier with its cathode follower connected to an audiomonitor and oscilloscope. Electrodes were fixed to the skull only when spike activity exhibited at least a 3:1 signal to noise ratio; Otherwise, the electrode was lowered in the steps of 5 to 10 µm increments until a 3:1 ratio spike activity was observed, to maximum depth of 6.6 mm below the skull [28,[36][37][38][39][40][41][42][43]. The copper pins were inserted into an Amphenol plug which was fixed onto the skull with dental acrylic cement.…”
Section: Surgerymentioning
confidence: 99%
“…LC neurons are electrophysiologically quiet during low vigilance states such as sleep or in the lack of sensory input, while the LC neurons markedly increase their firing rate during active walking or when exposed to a salient stimulus [13][14][15][16]. It has been reported that acute MPD administration increases the locomotor activity in a dose dependent manner [17][18][19][20][21][22][23][24][25][26][27] as well the LC neuronal activity [28] in freely moving rats. Considering the function of LC in vigilance and attention, we hypothesize that the LC neurons may play an important role in the behaviors induced by chronic MPD administration.…”
Section: Introductionmentioning
confidence: 99%